Kemampuan Klasifikasi dan Kolaborasi Siswa Pada Materi Klasifikasi Tumbuhan Menggunakan Pembelajaran Scientific Outbound: Studi Pendahuluan - Widya Cristanti; Topik Hidayat; Bambang Supriatno (Jurnal Penelitian Pendidikan IPA, 2024)
This research is a quantitative descriptive analysis which aims to describe the implementation of scientific outbound learning on plant classification material to see students' classification and collaboration abilities using data obtained objectively. The research was conducted in the botanical garden of the Indonesia University of Education with class X students at Daarut Tauhid Girl’s Boarding High School Bandung as research subjects. The research instruments used were a questionnaire assessing the design of scientific outbound learning, classification ability questions, as well as questionnaires and observation sheets of collaboration ability. The results of the research show that students' classification abilities are not yet optimal as seen through the pretest results, with an average of 38.13 and the posttest results with an average of 50.93 have not passed the school's KKM figure of 76 due to several obstacles and causal factors found, such as reduced students interest after learning is completed, lack of motivation given to students, and limited use of smartphones. Students' collaboration abilities are indicated to emerge through scientific outbound learning activities based on the results of students' collaboration abilities assessment which are already included in the category of developing collaboration abilities and already possessing collaboration abilities